1992
DOI: 10.1002/oms.1210271015
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric studies of the path of carbon in photosynthesis: Positional isotopic analysis of 13C‐labelled 2‐octulose phosphates

Abstract: The electron impact mass spectrometric fragmentation patterns of the per-0-trimethylsilyl (TMS) and alkoxime-TMS derivatives of D-glyCerO-D-UftrO and D-glycero-D-ido-octulo~ were fully analysed using seven specifically labelled 13C analogues. Many of the more intense ions in the spectra of the per&-TMS furanose and pyranose derivatives have more than one origin. On the other hand, the mass spectra of the straight-chain methoxime and ethoxime hepta-0-TMS derivatives contain ions each of which in general origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…2a), whereas Fig. 2c shows a mass spectrogram of the products of the in vitro assay and of an octulose standard, which corresponds with the fragmentation pattern predicted by Irvine et al (1992). Transketolase activity from 28-h rehydrated leaves was tested with glucose-6-phosphate and ribose-5-phosphate, respectively, as acceptor substrate.…”
Section: Transketolase Enzyme Activitiesmentioning
confidence: 70%
See 1 more Smart Citation
“…2a), whereas Fig. 2c shows a mass spectrogram of the products of the in vitro assay and of an octulose standard, which corresponds with the fragmentation pattern predicted by Irvine et al (1992). Transketolase activity from 28-h rehydrated leaves was tested with glucose-6-phosphate and ribose-5-phosphate, respectively, as acceptor substrate.…”
Section: Transketolase Enzyme Activitiesmentioning
confidence: 70%
“…Octulose puriWed from C. plantagineum leaves and the dephosphorylised substance yielded from the in vitro enzymatic assay using hydroxyl pyruvate acid were analysed using GC/MS. The fragmentation pattern reported by Irvine et al (1992) was used as reference for the veriWcation of the main fragments of the octulose standard and the octulose of the in vitro enzymatic assay about 4% of the activity measured with ribose-5-phosphate which points to a small amount of this active transketolase.…”
Section: Transketolase Enzyme Activitiesmentioning
confidence: 99%
“…From a mechanistic point of view, it is concluded that the sites 1,6,6' of glucose which are the most sensitive to the photosynthetic metabolism are those which are directly related to sites 1 and 5 of the ribulose 1,5-bis phosphate (Irvine et al, 1992). In contrast, the other sites, 2 to 5, of glucose which undergo a levelling effect are introduced in the course of reduction steps with NADPH or are engaged in exchange processes with water in specific isomerization reactions involving the three or six carbon intermediate molecules of the photosynthetic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were then dephosphorylated using human prostatic acid phosphatase, which was chosen for its ability to catalyze dephosphorylation quantitatively without causing the transformations produced by other phosphatases (Irvine et al. 1992). Dephosphorylation of up to 0.5 μmoles of sugar phosphates was carried out by the addition of 0.5 units of prostatic acid phosphatase to the sugar phosphate solution in 0.1 M ammonium acetate–acetic acid buffer pH 4.6 (typically 200 μl) and incubated for 24 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Only fragment ions which had been found to have essentially a single origin as the result of the GC/MS analysis of specifically 13 C-labelled sugar standards were used in this study (Irvine et al. 1992; MacLeod et al. 2001).…”
Section: Methodsmentioning
confidence: 99%